1971
DOI: 10.1104/pp.48.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Microbodies (Glyoxysomes and Peroxisomes) in Cucumber Cotyledons

Abstract: The changes in activities of glyoxysomal and peroxisomal enzymes have been correlated with the fine structure of micro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
1

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(68 citation statements)
references
References 39 publications
(36 reference statements)
7
60
0
1
Order By: Relevance
“…Enzyme profiles for two cucumber strains essentially agreed with those documented by Trelease et al (14) for cucumber cotyledon development. Isocitrate lyase activity (a glyoxysomal marker) rose in the dark during the first few days after planting, reaching a maximum at day 3, after which it declined.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Enzyme profiles for two cucumber strains essentially agreed with those documented by Trelease et al (14) for cucumber cotyledon development. Isocitrate lyase activity (a glyoxysomal marker) rose in the dark during the first few days after planting, reaching a maximum at day 3, after which it declined.…”
Section: Resultssupporting
confidence: 77%
“…There is good evidence for the degradation of glyoxysomes and de novo synthesis of peroxisomes during the functional transition (7). On the other hand, others have provided equally good evidence that there is a single, ongoing population of microbodies (2,14).…”
Section: Discussionmentioning
confidence: 95%
“…During photomorphogenesis, as seedlings undergo the transition from heterotrophic to autotrophic growth, organelles involved in photosynthesis and related functions (such as photorespiration) need to develop and genes required in these processes need to be activated. It was suggested that, during such a transitional stage, glyoxysomes are converted into leaf peroxisomes by replacement of glyoxysome-specific enzymes with those characteristic of leaf-type peroxisomes (Trelease et al, 1971;Olsen and Harada, 1995). In this study, we observed in Arabidopsis seedlings peroxisome elongation after 0.5-h light exposure, constriction and fission of these organelles at 2 h, and a sheer increase in peroxisome abundance at 4 and 8 h (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The effect of transfer to light at various stages of growth in the dark on glycolate oxidase, hydroxypyruvate reductase, catalase, and isocitrate lyase have been described in this material (32). In cucumber cotyledons too, changes in enzymes of the glyoxylate cycle and those of leaf peroxisomes have been measured during greening under light-dark cycles and after transfer to light after 5 days in darkness (35). Furthermore, it is known from the work of Van Poucke and his associates (36,37) that the development of glycolate oxidase and glyoxylate reductase in cotyledons of Sinapis seedlings is under the control of the phytochrome system as it is in the young developing leaves of Phaseolus (11, 23) and also, apparently, of wheat (8).…”
mentioning
confidence: 99%
“…leaves have been examined (7-11, 23, 24, 33, 34), and some information is available for the special case of cotyledons of fatty seedlings (14,17,22,32,(35)(36)(37). Particular interest attaches to those enzymes characteristic of microbodies, since during fat utilization one class of microbody, the glyoxysome, is present, whereas during greening, leaf peroxisomes appear.…”
mentioning
confidence: 99%